Observations of Igneous Subsurface Stratigraphy during the Jezero Crater Floor Rapid Traverse from the RIMFAX Ground-penetrating Radar - Emileigh S. Shoemaker Thackston; Titus M. Casademont; Lynn M. Carter; Patrick Russell; Henning Dypvik; Sanna Alwmark; Briony H. N. Horgan; Hans E. F. Amundsen; Sigurd Eide; Svein-Erik Hamran; David A. Paige; Sanjeev Gupta; et al. (The Planetary Science Journal)
Perseverance traversed the eastern, northern, and western margins of the Séítah formation inlier on the rover’s western fan front approach. Mapping the stratigraphy and extent of the Máaz and Séítah formations is key to understanding the depositional history and timing of crater floor resurfacing events. Perseverance's rapid progress across the Jezero crater floor between the Octavia E. Butler landing site and the western fan front resulted in limited contextual images of the deposits from the Navigation Camera and Mast Camera Zoom. By combining the limited surface images with continuous subsurface sounding by the Radar Imager for Mars’ Subsurface Experiment (RIMFAX) ground-penetrating radar, Jezero crater floor stratigraphy was inferred along this rapid traverse. We produced the first subsurface map of the Máaz formation thickness and elevation of the buried Séítah formation for 2.3 km of the rapid traverse. Three distinct reflector packets were observed in RIMFAX profiles interspersed with regions of low-radar reflectivity. We interpret these reflector packets with increasing depth to be the Roubion member of the Máaz formation (covered in places with regolith), the Rochette member, and the Séítah formation. We found a median permittivity of 9.0 and bulk density of 3.2 g cm ^−3 from hyperbola fits to RIMFAX profiles, which suggests a mafic composition for Máaz and Séítah. The low-radar reflectivity regions within each reflector packet could indicate potential depositional hiatuses where low-density material like sediment or regolith could have accumulated between successive Máaz formation lava flows and the Séítah formation at depth.